Standard vs. expectation-based indices of TOT volatility in Argentina and other land-abundant countries - Arrufat, José Luis (2014)
Fil: Arrufat, José Luis. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.